Growth and development of yacon in different periods of planting and growing regions - Diego Mathias Natal da Silva; Fábio Luiz de Oliveira; Paulo Cezar Cavatte; Mateus Augusto Lima Quaresma; Bruno Fardim Christo (Acta Scientiarum. Agronomy, 2018)
The increasing interest in the commercial exploitation of yacon has demanded adequate technological knowledge for the implantation and management of the crop, including planting periods and cultivation regions that contribute to the satisfactory growth and development of the species. This study was conducted in two different locations, one in a mountainous region and another in a lowland region. In each location, yacon was planted in four different seasons, fall (April), winter (July), spring (September) and summer (December). We collected primary dry matter accumulation data for different parts of the plant and the leaf area at 30 day intervals. We used these values to calculate the following morphophysiological indexes: specific leaf area, leaf area index, tillage growth rate and net assimilation rate. We concluded that planting in the fall in mountainous or lowland sites favoured the growth and development of yacon. Cultivation in mountainous regions, regardless of the planting season, promoted a greater mass accumulation of tuberous roots, which may be reflected in higher productivity. Both fall and winter planting in the mountainous region allows root harvesting at the same time.